Blends of carboxylate acid polymer based on high-density polyethylene with nylon : effect of zinc neutralized versus acid form HDPE-g-MAH - Benjamaad Chartrenuwat (Chulalongkorn University, 2014)
Thesis (M.Sc.)--Chulalongkorn University, 2006